Ciclo de KOLB como estrategia metodológica para el proceso enseñanza aprendizaje de biología en la Unidad Educativa General Leónidas Plaza Gutiérrez, periodo mayo octubre 2022. - Catota Toapanta, Silvia Paulina (2025)
The educational process needs to be dynamic, interactive, motivating, innovative, and of quality. The present research will determine the importance of the Kolb Cycle as a methodological strategy in the teaching-learning process of Biology for students of the Intensive Baccalaureate in the General Educational Unit Leónidas Plaza Gutiérrez. This research design was quasi-experimental, with a quantitative approach based on numerical and statistical analysis of field research. A written test was applied to the students, which diagnosed their level of knowledge in the area of Biology. Subsequently, the proposal was developed with the students, and based on the experience, it was shown that they achieved significant and quality learning.